SEGMENTASI GAYA HIDUP PADA MAHASISWA EKONOMI SYARIAH - Zuraidah; Edi Subiyantoro (Istithmar: Jurnal Studi Ekonomi Syariah, 2018)
The concept of lifestyle is still commonly used to assist in the mapping of consumer behavior and market segmentation. Market segmentation is an attempt to divide the market into groups that can be distinguished from each other in case of need, characteristics or behavior. Segmentation study in Economics of Syari’ah STAIN Kediri used to collect information on the characteristics of the students. Such information can be used to develop a variety services to students in the future. Cluster analysis in this study uncovered that there are three groups of students that is dynamic, homebody, and passive.